Bahay ni Lola - Alvarez, Patricia Anne G. (Animo Repository, 2021)
Bahay ni Lola is a Traditional and Fusion Cuisine Restaurant that aims to provide good quality and nutritious dishes that are affordable to fund our advocacy of raising awareness of the agricultural crisis happening to Filipino farmers. The business aims to support its mission by creating a sustainable social business that provides work to persons with disabilities and at-risk young adults in the business locale by partnering with local social organizations. The business will operate under the form of a corporation type of business structure that is separate and distinct from its owners in the form of a restaurant and caters to dine-in and delivery. This form of business directly helps sustainable acquisition of ingredients for our farm-to-table movement. The market for fusion Filipino food has a promising future as statistics show that growth in this market is considerable per food trends. The business distinguishes itself by providing service with its mix of traditional and fusion Filipino cuisine with an atmosphere of ancestral Bahay na Bato with artifacts that make the customers feel like they are back in their lola or grandmother’s house. The business projects a capital of ₱75,000 along with a budget of ₱15,000 annually for product development of dishes. This will be sourced from the business stakeholders in equal amounts for an equal number of shares and ownership. To date, the company is gathering funds and awaiting a suitable time to launch the business.